Tenofovir resistance in early and long-term treated patients on first-line antiretroviral therapy in eight low-income and middle-income countries. (1st November 2020) - Inzaule, Seth C.; Jordan, Michael R.; Cournil, Amandine; Girón-Callejas, Amalia; Avila-Rios, Santiango; Mulenga, Lloyd; Ssemwanga, Deogratius; Asio, Juliet; Diop-Ndiaye, Halimatou; Niasse-Traore, Fatou; Nhan, Do T.; Dat, Vu Q.; et al.
Abstract : Objective: We aimed to assess the frequency of tenofovir (TDF) resistance in people failing tenofovir/lamivudine or emtricitabine (XTC)/nonnucleotide reverse-transcriptase inhibitor-based first-line antiretroviral treatment (ART) using data from 15 nationally representative surveys of HIV drug resistance conducted between 2014 and 2018 in Cameroon, Guatemala, Honduras, Nicaragua, Senegal, Uganda, Vietnam and Zambia. Methods: Prevalence of nucleoside reverse-transcriptase inhibitor resistance among participants with virological nonsuppression (viral load ≥1000 copies/ml) who had received TDF-based ART for 12–24 months (early ART group) and at least 40 months (long-term ART group) was assessed using Sanger sequencing and resistance was interpreted using the Stanford HIVdb algorithm. For each group, we estimated a pooled prevalence using random effect meta-analysis. Results: Of 4677 participants enrolled in the surveys, 640 (13.7%) had virological nonsuppression, 431 (67.3%) were successfully genotyped and were included in the analysis; of those, 60.3% (260) were participants in the early ART group. Overall, 39.1, 57.9, 38.5 and 3.6% patients in the early ART group and 42.9, 69.3, 42.9 and 10.0% patients on long-term ART had resistance to TDF, XTC, TDF + XTC and TDF + XTC + zidovudine, respectively. Overall, tenofovir resistance was mainly due to K65R or K70E/G/N/A/S/T/Y115F mutations (79%) but also due to thymidine analogue mutations (21%) which arise from exposure to thymidine analogues but causing cross-resistance to TDF. Conclusion: Dual resistance to TDF + XTC occurred in more than 40% of the people with viral nonsuppression receiving tenofovir-based first-line ART, supporting WHO recommendation to optimize the nucleoside backbone in second-line treatment and cautioning against single drug substitutions in people with unsuppressed viral load.